The Exchange of agricultural products and inputs and its performance in financial management. Case study: concentrados Valera, C.A. 2022-2023 (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2024)
The general objective of this study is: To evaluate the implementation of the Agricultural Products and Inputs Exchange in the financial management of the company Concentrados Valera, C.A, in the period 2022-2023. With the following specific objectives: Characterize the performance of process management in the treasury area and its strategic value in the finances of the company Concentrados Valera, C.A., describe the decision- making process in negotiations through the Agricultural Exchange in the company Concentrados Valera, C.A, explore the opportunities offered by the Agricultural Exchange and its contribution to the finances of the company under study, determine the efficiency of the use of the agricultural exchange and its contribution to the expenditure of Concentrados Valera C.A, with reference to the purchase of raw materials for the production of balanced animal feed. The design is of a documentary and field type, of an evaluative nature, under a qualitative-quantitative approach with a non-experimental- longitudinal design. The semi-structured interview technique was applied to 5 people with strategic positions and an observation guide (checklist) with the support of the ISO 9004:2018 Standard tool questionnaire. Likewise, two Brokerage Houses were interviewed to directly explore the perspective of opportunities. The results of the research showed strengths in decision-making aimed at the efficient use of resources (Exemption from IGTF and bank commissions), and it was also demonstrated that the Agricultural Stock Exchange is an opportunity for Venezuelan companies in the Agricultural sector to guarantee their security. economic and a calculated risk, however, the waiting times and the administrative process are bureaucratic.
Keywords: agricultural stock exchange; efficiency; effectiveness; financial management